Antecedents of Impulsive Buying among Moslems: The Mediation Role of FOMO - Sari, Puspa Novita (Li Falah: Journal of Islamic Economics and Business, 2023)
The evolution of technology and shifts in consumer behavior have caused significant changes in the business landscape. One intriguing phenomenon that has emerged from these shifts is the practice of live-streaming shopping. This study aims to investigate the factors that impact impulsive purchasing among Muslims during live-streaming shopping sessions. The study's participants are individuals who have made purchases of Zoya products through live-streaming broadcasts on the TikTok app, with a total of 172 respondents. The data analysis method employed is the structural equation model (SEM) using the Smart PLS software. The findings of the research indicate that the fear of missing out (FOMO) acts as a mediator in the relationship between scarcity and impulsive buying. At the same time, social media usage mediates the connection between social media usage and impulsive buying. This finding implies that scarcity and social media usage can amplify impulsive buying tendencies during live-streaming shopping when influenced by the fear of missing out (FOMO).